Simulation Modelling and Strategic Change: Creating the Sustainable Enterprise - Dawson, Patrick; Spedding, Trevor (Australasian Journal of Information Systems, 2010)
This paper highlights the benefits of using discrete event simulation models for developing change management frameworks which facilitate productivity and environmental improvements in order to create a sustainable enterprise. There is an increasing need for organisations to be more socially and environmentally responsible, however these objectives cannot be realised in isolation of the strategic, operations and business objectives of the enterprise. Discrete Event Simulation models facilitate a multidimensional approach to enterprise modelling which can integrate operations and strategic considerations with environmental and social issues. Moreover these models can provide a dynamic roadmap for implementing a change strategy for realising the optimal conditions for operational and environmental performance. It is important to note that the nature of change is itself dynamic and that simulation models are capable of characterising the dynamics of the change process. The paper argues that incorporating social and environmental challenges into a strategic business model for an enterprise can result in improved profits and long term viability and that a multidimensional simulation approach can support decision making throughout the change process to more effectively achieve these goals.